Analisis Penyediaan Rumah Sederhana dalam Dialektika Kapitalisme - Putri Halimah; Alghifari Mahdi Igamo (Department of Development Economics, Universitas Sriwijaya, 2019)
Home is a basic human need. In the Law of the Republic of Indonesia No.1 of 2011 states that housing or access to housing is a right for every community whose existence is the responsibility of the government. The problem that has occurred to this day is that there are still many people living in urban areas who have to occupy illegal or slum settlements. This is due, among other things, to the influence of land and housing prices which increase each year due to high demand which is also caused by the increasing population and urbanization rate. However, in reality the capitalists who control the housing sector are only fixated on capital accumulation by building and marketing homes to middle and high income people. As a result, low-income communities are marginalized in the suburbs, and build non-conventional settlements, slums and squatter. This study with the literature study method aims to analyze how to provide a home for low-income people in the dialectic of capitalism, by making the MBR as an important actor in the construction and provision of housing